2015
DOI: 10.1177/1534735415596570
|View full text |Cite
|
Sign up to set email alerts
|

Natural Products for Management of Oral Mucositis Induced by Radiotherapy and Chemotherapy

Abstract: Oral mucositis is a common side effect of systemic chemotherapy and radiotherapy of head and neck in patients with cancer. Severe oral mucositis is painful and affects oral functions, including intake of food and medications and speech. Prevention of oral mucositis affects the life quality of patients. Recent studies have been focused on natural products to improve or reduce this complication. Many clinical trials have been performed to assess natural products for treatment of mucositis and their results are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 66 publications
(102 reference statements)
0
28
0
7
Order By: Relevance
“…According to this proposal, it is suggested that the formation of ROS arising from the action of CT and RT would be capable of generating an oxidant–antioxidant imbalance and thereby activate proinflammatory cytokines responsible for tissue damage. Therefore, different strategies of prevention and treatment of OM have been aimed at the control of OS …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to this proposal, it is suggested that the formation of ROS arising from the action of CT and RT would be capable of generating an oxidant–antioxidant imbalance and thereby activate proinflammatory cytokines responsible for tissue damage. Therefore, different strategies of prevention and treatment of OM have been aimed at the control of OS …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, different strategies of prevention and treatment of OM have been aimed at the control of OS. 1,4,5,7,27,28 Cannabidiol Cannabis sativa, popularly known as marijuana, is the most used illegal drug in the world and can be associated with many health problems. This plant contains over 545 substances, which have different effects in the body.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…İçerdiği bileşiklerin antienflamatuar, antibakteriyel, spazmolitik, sedatif ve antifungal özelliğe sahip olduğu klinik öncesi araştırmalarda gösterilmiştir. [33] Literatürde papatyanın oral mukozada granulasyon ve epitelizasyonu hızlandırdığı belirtilmekle birlikte, kanser tedavisine bağlı oral mukozit üzerindeki etkisini değerlendiren araştırmaların sayısı sınırlıdır ve birbirleriyle çelişen sonuçlar içermektedir. [14,34] Klinik öncesi bir araştırmada, papatyanın ratlarda 5-FU ilişkili oral mukozit tedavisinde iyileştirici etkisi olduğu belirtilmiştir.…”
Section: Papatya (Matricaria Chamomile)unclassified
“…[53] Literatürde esansiyel yağların cilt ve mukoza enfeksiyonlarının tedavisinde kullanıldığı belirtilmekle birlikte oral mukozit yönetiminde kullanımı ile ilgili az sayıda araştırma mevcuttur ve örneklem büyüklükleri sınırlıdır. [22,33,54,55] Melaleuca alternifolia (çay ağacı), citrus bergamia (bergamot), ve pelargonium graveolens (ıtır çiçeği) esansiyel yağ karışımının etkinliğinin araştırıldığı bir çalışmada, tüm yağlar birer damla olacak şekilde yarım bardak suya eklenerek karıştırılmış ve hastalardan günde 5 kez bu solüsyonla gargara yapmaları istenmiştir. Araştırma sonucunda, karışımın radyoterapi ilişkili oral mukoziti önlemede etkili olmadığı bulunmuştur.…”
Section: Antioksidan Vitaminlerunclassified
See 1 more Smart Citation